2014
DOI: 10.1088/1748-9326/9/1/015003
|View full text |Cite
|
Sign up to set email alerts
|

Glacier area changes in Northern Eurasia

Abstract: Glaciers are widely recognized as key indicators of climate change. Recent evidence suggests an acceleration of glacier mass loss in several key mountain regions. Glacier recession implies landscape changes in the glacial zone, the origin of new lakes and activation of natural disaster processes, catastrophic mudflows, ice avalanches, outburst floods, etc. The absence or inadequacy of such information results in financial and human losses. A more comprehensive evaluation of glacier changes is imperative to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 18 publications
1
33
0
2
Order By: Relevance
“…The current investigation revealed that he missed some small glaciers, particularly in the Bzipi, Kodori, Rioni, Enguri and Tergi (Terek) river basins. Khromova et al (2009Khromova et al ( , 2014 used manually digitized results to estimate changes of more than 1200 glaciers in the Caucasus in two periods : 1911-1957 and 1957-2000. They found that glacier area decreased from 1911 to 1957 by 24.7 % (0.52 % yr −1 ) and from 1957 to 2000 by 17.7 % (0.41 % yr −1 ). Elbrus glaciers lost 14.8 % (0.31 % yr −1 ) and 6.3 % (0.14 % yr −1 ) respectively for the two time periods.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The current investigation revealed that he missed some small glaciers, particularly in the Bzipi, Kodori, Rioni, Enguri and Tergi (Terek) river basins. Khromova et al (2009Khromova et al ( , 2014 used manually digitized results to estimate changes of more than 1200 glaciers in the Caucasus in two periods : 1911-1957 and 1957-2000. They found that glacier area decreased from 1911 to 1957 by 24.7 % (0.52 % yr −1 ) and from 1957 to 2000 by 17.7 % (0.41 % yr −1 ). Elbrus glaciers lost 14.8 % (0.31 % yr −1 ) and 6.3 % (0.14 % yr −1 ) respectively for the two time periods.…”
Section: Previous Studiesmentioning
confidence: 99%
“…In the recent past, results of glacier monitoring activities in Central Asia (except Kazhakstan and China) are mainly based on remote sensing techniques with a focus on geodetic area and volume change assessments (see Table 4) or front variation measurements (Aizen et al, 2007;Konovalov and Desinov, 2007;Niederer et al, 2007;Haritashya et al, 2009;Kääb et al, 2015;Narama et al, 2010;Hagg et al, 2013;Kriegel et al, 2013;Gardelle et al, 2013;Gardner et al, 2013;Ozmonov et al, 2013;Pieczonka et al, 2013;Khromova et al, 2014;Pieczonka and Bolch, 2015;Farinotti et al, 2015;Petrakov et al, 2016). Between 1994 and 1998, most of the in situ glacier observation programmes were discontinued.…”
Section: Investigations At Individual Monitoring Sitesmentioning
confidence: 99%
“…1). The first attempts to estimate the extent of the region's glaciers were published as part of the "Catalogue of Glaciers in the USSR, volume 20" (Vinogradov, 1968;Khromova et al, 2014). This was based on observations from topographic maps and aerial imagery captured in the early 1950s (various years), supplemented by field studies (Kotlyakov, 1980).…”
Section: Glaciersmentioning
confidence: 99%
“…The Kamchatka Peninsula is of particular interest because investigation of its recent glacial history has been limited (cf. Khromova et al, 2014;Earl and Gardner, 2016), despite being the largest glacierised area in NE Asia (Solomina et al, 2007) and a region where glaciers, climate and active volcanoes currently interact (Barr and Solomina, 2014).…”
Section: Introductionmentioning
confidence: 99%